A Versatile Resilience Packet Ring Protocol Model for Homogeneous Networks - Minhas, Tayyeba; Khan, Shawal; Arslan, Farrukh; Ali, Anum; Hussain, Aamir; Ali, Jehad (Applied Sciences (Switzerland), 2023)
Optimizing routes and paths improves network performance. Due to the encapsulation and tunneling of the packets, mobile IP-based communication contributes to packet drops or significant delays between the sender and receiver. Packet loss during handoff reduces TCP throughput as well. One solution is to use the IEEE 802.11 Medium Access Control (MAC) protocol and TCP or UDP models to increase routing protocol performance. In the linkage of homogeneous networks, it is challenging to determine route failure. In addition, the 802.11 MAC also uses a link connection. As a result, re-covering the entire route path takes a longer time. Thus, improving wired and wireless mobile node communication and handover is both challenging and critical. To overcome this challenge, we propose to use the Versatile Resilience Packet Ring protocol (VRPR)-based model. In this paper, we propose a novel VRPR-based network model that allows uninterrupted communication in both wired and wireless media. VRPR is used in the network layer to avoid buffer overflow and client mobility. Our new model also identifies the cause of the route failure, whether it is due to client mobility (handover), due to link breakage (channel degradation), or due to buffer overflow. We evaluate our network model based on three performance factors, namely, the delay, packet, and packet loss, and compared it between wired and wireless media. Our Enhanced-VRPR-based network model outperforms the current VRPR wired and wireless network models. We validate our model through OMNet++ simulations.
Keywords: packet buffering; route optimization; versatile resilience packet ring protocol